Enhancing Students’ Critical Thinking in Physics Using Graphic Organizer-Enhanced and Context-Based Learning Strategies - Achor, Emmanuel E.; Jack, Gladys U.; Uzomah, Theophilus N. (Journal of Research in Science and Mathematics Education, 2024)
Purpose: This study focused on fostering critical thinking in physics using graphic organizer-enhanced and context-based learning strategies among secondary students in Taraba State, Nigeria. Methodology: Five objectives guided the study using a quasi-experimental design. The sample comprised 225 students (males=113, females= 112). Data were collected using the Test of Critical Thinking Skill Acquisition (TOCTSA). The Kendal Tau-b inter-rater formula was used to determine the reliability of TOCTSA. Mean, standard deviation, and ANCOVA were the statistical methods employed. Findings: The study revealed a significant difference in the mean critical thinking scores in physics for students taught using the graphic organizer-enhanced learning strategy compared to those taught using the conventional strategy (F1,172 = 174.230; p = 0.000 < 0.05), as well as for those taught using the context-based learning strategy compared to the conventional strategy (F1,169 = 7.772; p = 0.006 < 0.05). However, there was no significant difference in the mean score of critical thinking in physics between male and female students taught using the graphic organizer-enhanced strategy (F1, 50 = 2.897; p = 0.095 > 0.05). Conversely, there was a significant difference in the mean score of critical thinking in physics between male and female students taught using the context-based learning strategy (F1,47 = 17.578; p = 0.000 < 0.05). Significance: These strategies have the potential to enhance the academic achievement of both male and female students and promote the acquisition of critical thinking skills in physics.